(untitled) - Shao, Yunfan; Hourdin, Lysandre; Sanchez, Jean-Yves; Iojoiu, Cristina (Comptes Rendus. Chimie, 2025)
Electrochemical energy storage and conversion systems, such as rechargeable lithium batteries and fuel cells, are considered to be nexuses that link chemical and electrical energies. To achieve efficient, safe, and sustainable energy storage and conversion, many new materials must be designed, synthesized, and tested. Among these, fluorinated organic and inorganic materials play a key role. The highly electronegative fluorine atoms give these materials exceptional stability against degradation, as well as improved performance in electrochemical processes and the development of next-generation solid-state batteries, PEMFC and electrolyzers. In this article, we provide a brief overview of our recent work on fluorinated materials developed at the Laboratory of Electrochemistry and Physical-Chemistry of Materials and Interfaces (LEPMI, Grenoble). These include new salts, solvents, separators, binders, polymer electrolytes, etc. for batteries and fuel cells. We hope that this article will raise awareness of the importance of fluorinated synthons, molecules and materials in electrochemical energy sources, especially given the serious environmental concerns surrounding PFAS compounds.